THE EFFECT OF HEALTH COUNSELLING USING EDUCATIONAL VIDEOS ON CHANGES IN ELDERLY KNOWLEDGE ABOUT GOUTY ARTHRITIS IN KUTA KRUENG VILLAGE - Nurhayati Ningsih; Dedi Irawan; Ayu Nalita; Nurul Maulidya (Universitas Bina Bangsa Getsempena, 2025)
Elderly people are individuals over 60 years old, who are susceptible to various diseases due to declining body function. The increasing number of elderly people is accompanied by the risk of degenerative diseases, such as hypertension, stroke, gouty arthritis, and heart disease. Gout arthritis is caused by high levels of purine in the body and can affect all ages if the diet is unhealthy. The purpose of this study was to determine the effect of health education using educational videos on changes in elderly knowledge about gout arthritis in Kuta Krueng village. This study is an experimental study with a One-Group Pre-post Test Design approach, the number of samples in this study was taken from the elderly population in Kuta Krueng village as many as 47 respondents. In this study, a bivariate analysis was conducted to prove the research hypothesis. The results of the T-test obtained a P value = 0.000. meaning that there is an effect of health education using educational videos on changes in elderly knowledge about gout arthritis in Kuta Krueng Village. Using the Dependent T-test at a significance level of 95% (= 0.05) and a paired t-test with a p-value of 0.000, the results showed a significant difference in the knowledge of the elderly before and after counseling. It is recommended to provide health education about gout to the elderly periodically through counseling and educational media. This step aims to increase the elderly's knowledge and reduce the prevalence of gout in the future.